2012
DOI: 10.1590/s1983-51752012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Reconstrução palpebral com enxerto de cartilagem autóloga de concha de orelha

Abstract: Eyelid repair using an autologous conchal cartilage graft Eyelid repair using an autologous conchal cartilage graft Reconstrução palpebral com enxerto de cartilagem autóloga de concha de orelha ABSTRACT Background: In this study, we evaluated the results obtained with Matsuo's technique for eyelid reconstruction at the Clínica de Cirurgia Plástica do Hospital Felício Rocho (Plastic Surgery Clinic of the Hospital Felício Rocho) from December 1992 to May 2011. Furthermore, we performed a nonsystematic review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We considered that by applying regional skin flaps which diminished long-term retraction and ectropion. Matsuo technique to reconstruct lower lid defects, which had been used by Alves et al (2012), is commonly accepted [7,8]. Though, chonderitis and conjunctivitis seem to be annoying, and in scare situations caused severe infections, our results again confirmed that providing well-nourished flaps over cartilage may protect it from inflammation and destruction and even sever cornea irritation.…”
Section: Discussionsupporting
confidence: 71%
“…We considered that by applying regional skin flaps which diminished long-term retraction and ectropion. Matsuo technique to reconstruct lower lid defects, which had been used by Alves et al (2012), is commonly accepted [7,8]. Though, chonderitis and conjunctivitis seem to be annoying, and in scare situations caused severe infections, our results again confirmed that providing well-nourished flaps over cartilage may protect it from inflammation and destruction and even sever cornea irritation.…”
Section: Discussionsupporting
confidence: 71%
“…We considered that by applying regional skin flaps which diminished long-term retraction and ectropion. Matsuo technique to reconstruct lower lid defects, which had been used by Alves et al (2012), is commonly accepted [7,8]. Though, chonderitis and conjunctivitis seem to be annoying, and in scare situations caused severe infections, our results again confirmed that providing well-nourished flaps over cartilage may protect it from inflammation and destruction and even sever cornea irritation.…”
Section: Discussionsupporting
confidence: 71%
“…The eyelid reconstruction technique is chosen Local and regional flaps are useful for reconstruction of the lamella. Flaps, as described previously by Tenzel, Hughes, Mustardé, and Cutler, are well known among plastic surgeons and are useful for reconstruction of large defects, as well as cartilage grafts [1][2][3][4][5][6] . Tarsus with free margin associated with myocutaneous flap can be used for reconstruction of the posterior lamella.…”
Section: Discussionmentioning
confidence: 99%